(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
The moment it was released, Guillermo del Toro’s film, Pan’s Labyrinth became an instant hit due to its visuals and atmosphere. However, the work is far more valuable than what the general public perceives of it, as it incorporates parts of humanity’s cultural heritage. Published film reviews and studies do not penetrate the essence of the work. In the course of my research, I have revealed the system of symbols that leads through the cultural history of humanity, from archaic religions through Dante’s Divine Comedy to the Spanish Civil War. The unfolding meaning parallelly presents the process of childhood awareness and becoming an adult. Using the results of my research, I developed a method of multidisciplinary film analysis that supports student autonomy and facilitates cooperative learning. The method can be applied both in secondary education and higher education.